DETERMINANTS OF WOMEN'S PARTICIPATION IN MICROFINANCE INSTITUTIONS - Isra Yeni; Yollit Permata Sari; Urmatul Uska Akbar; Dwirani Puspa Artha; Hari Setia Putra (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2023)
ABSTRACTMicrofinance institutions are an alternative for women who need business credit loans. Through business credit loans, it opens opportunities for women to increase household income. This study aims to analyze the effect of household income on women's opportunities to make business credit loans in Indonesia. The data used in this study was from SUSENAS in 2016, while the model used in this study is the logit model. Variables in the logit model have a binary nature. The binary dependent variable in this study is women who choose to make business credit loans or not to make business credit loans. The results of the study shows that household income, age of the head of the household, employment status of the head of the household, status of home ownership, and area have a significant effect on the opportunities for women to participate in business credit loans. Through these results, the policy recommendation from this study is to provide support for women to develop microcredit businesses through business credit loans.Keywords: Household Income, Microfinance, Women ParticipationABSTRAKLembaga keuangan mikro menjadi alternative bagi perempuan yang membutuhkan pinjaman kredit usaha. Melalui pinjaman kredit usaha membuka peluang bagi perempuan untuk meningkatkan pendapatan rumah tangga. Dengan demikian penelitian ini bertujuan untuk menganalisis pengaruh pendapatan rumah tangga terhadap peluang perempuan untuk melakukan pinjaman kredit usaha di Indonesia. Data yang digunakan adalah data SUSENAS 2016 di Indonesia. Model yang digunakan dalam penelitian ini adalah logit model. Variabel dalam model logit memiliki sifat biner. Variabel Dependen yang bersifat biner dalam penelitian ini adalah wanita yang memilih melakukan pinjaman kredit usaha atau tidak melakukan pinjaman kredit usaha. Hasil penelitian menjelaskan bahwa pendapatan rumah tangga, umur kepala rumah tangga, status pekerjaan kepala rumah tangga, status kepemilikan rumah, dan wilayah berpengaruh signifikan terhadap peluang wanita berpatisipasi pada pinjaman kredit usaha. Melalui hasil tersebut maka rekomendasi kebijakan dari penelitian ini adalah memberi dukungan kepada perempuan untuk mengembangkan usaha kredit mikro melalui pinjaman kredit usaha.Kata Kunci: Keuangan Mikro, Logit Model, Pendapatan Rumah Tangga